Pengalaman Clinical Instructor dalam membimbing mahasiswa keperawatan di RSU Dr. Slamet Garut - Iwan Wahyudi; Roganda Situmorang (Jurnal Medika Cendikia, 2018)
The Aims of this study to gain depth understanding of the experience of Clinical Instructor in guiding nursing students in dr.Slamet Garut Hospital. This research used a qualitative study with a phenomenological approach. This study included 6 clinical instructor as an informan The results of this study identify five main themes: (1) The mechanism appointment of Clinical Instructor , (2) Impact of Being a Clinical Instructor assignment, (3) Responsibility A Clinical Instructor, (4) Barriers In Process Guidance, (5) Hope of Clinical Instructor. Recommendations from this study are expected absence of nursing management system against labor Comprehensive for Clinical Instructor and Clinical Instructor working together with Instructor Academic of the educational institution to guide the students of nursing.